Comparison of the efficacy of intravenous tranexamic acid with and without topical administration versus placebo in urgent endoscopy rate for acute gastrointestinal bleeding: A double-blind randomized controlled trial. Issue 1 (February 2018) - Tavakoli, Nader; Mokhtare, Marjan; Agah, Shahram; Azizi, Ali; Masoodi, Mohsen; Amiri, Hassan; Sheikhvatan, Mehrdad; Syedsalehi, Bahare; Behnam, Behdad; Arabahmadi, Mehran; Mehrazi, Maryam
Background: Tranexamic acid (TXA), a synthetic antifibrinolytic drug, is effective as a treatment for serious hemorrhage, including bleeding arising from major trauma and post-operative interventions. Significant acute gastrointestinal bleeding may have a poor outcome despite routine medical and endoscopic treatments. The aim of this study was to assess whether early intravenous and/or intravenous plus topical administration of TXA reduces the need for urgent endoscopy for acute gastrointestinal bleeding. Method: This double-blind randomized clinical trial included 410 patients with proven acute gastrointestinal bleeding. All patients received conventional therapy. The subjects were randomized to three groups: (A) 138 patients received intravenous TXA (1 g q6h); (B) 133 patients received topical TXA (1 g single dose by nasogastric tube) plus systemic TXA; and (C) 139 patients received a placebo (sodium chloride 0.9%) for 24 hours. Subgroup statistical analyses were conducted for urgent endoscopy, mortality, re-bleeding, blood transfusion, endoscopic and/or surgical intervention rates, and health status. Results: The time to endoscopy was significantly shorter in group C (15.58 ± 7.994, p  < 0.001). A need for urgent endoscopy was seen in 14.49%, 10.52%, and 30.21% of patients in groups A, B, and C, respectively ( p  < 0.001). No significant statistical differences were seen between treatment groups regarding mortality, re-bleeding, blood transfusion, and endoscopic and/or surgical intervention rates. No thromboembolic event was documented during the 1-week follow up. Conclusions: Our results showed that the antifibrinolytic properties of TXA can aid in changing an urgent endoscopy to an elective procedure, with better outcomes for both physicians and patients.